PENGGUNAAN STATISTIK DALAM EVALUASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Achmad Rasyid Ridha; Taufiq Khoirin; Sriyanta (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
The evaluation of Islamic Religious Education (PAI) learning requires an objective, accurate, and data-based approach to measure students' cognitive, affective, and psychomotor achievements. This paper discusses the use of statistical applications as scientific instruments in improving the quality of PAI learning evaluation in the digital era. The purpose of this writing is to explain the definition, urgency, types of statistical applications, as well as their advantages and disadvantages in the context of PAI evaluation. The discussion covers five main statistical applications: Microsoft Excel for simple data processing and grade visualization, ITEMAN for item analysis based on Classical Test Theory, SPSS for validity and reliability testing of instruments and inferential analysis, SmartPLS for model testing based on PLS-SEM with latent variables, and LISREL for covariance-based structural analysis. The study results show that the use of statistical applications makes significant contributions to improving assessment objectivity, testing the quality of evaluation instruments, facilitating data-driven decision making, and increasing time efficiency and learning accountability. However, its implementation still faces obstacles such as low statistical literacy among teachers, limited facilities, and minimal professional training. This paper recommends the need to improve PAI teachers' competencies through continuous training, provision of technological infrastructure by schools and government, and strengthening of prospective PAI teacher curricula with applied statistics courses so that PAI learning evaluation becomes more scientific, effective, and relevant to the demands of contemporary development.